Analysis of Power Law Fluids and the Heat Distribution on a Facing Surface of a Circular Cylinder Embedded in Rectangular Channel Fixed With Screen: A Finite Element’s Analysis - Abid A. Memon (IEEE, 2021)
The current article is an understanding of heat transfer and non-Newtonian fluid flow with implications of the power-law fluid on a facing surface of the circular cylinder embedded at the end of the channel containing the screen. The cylinder is fixed with an aspect ratio of 4:1 from height to the radius of the cylinder. The simulation for the fluid flow and heat transfer was obtained with variation of the angle of screen $\frac {π }{6}\le θ \le \frac {π }{3}$ , Reynolds number 1000 ≤ Re ≤ 10, 000 and the power-law index $0.7\le n\le 1.3$ by solving two-dimensional incompressible Navier-Stokes equations and the energy equation with screen boundary condition and slip walls. The results will be in a good match with asymptotic solution given in the literature. The results are presented through graph plots for non-dimensional velocity, temperature, mean effective thermal conductivity, heat transfer coefficient, and the local Nusselt number on the front surface of the circular cylinder. It was found that the ratio between the input velocity to the present velocity on the surface of the circular cylinder remains consistent and reaches up to a maximum of 2.2% and the process of heat transfer does not affect by the moving of the screen and clearly with the raise of power-law indexes the distribution of the heat transfer upsurges. On validation with two experimentally derived correlations, it was also found that the results obtained for the shear-thinning fluid are more precise than the numerically calculated results for Newtonian as well as shear-thickening cases. Finally, we suggest necessary measures to enrich the development of convection when observing with strong effects influenced by the screens or screen boundary conditions.